A Family of Autoconnected Transformers for 12-and 18-Pulse Converters-Generalization for Delta and Wye Topologies - Fernandes, Rodolfo Castanho; Oliveira, Priscila da Silva [UNESP]; Seixas, Falcondes José Mendes [UNESP] (Institute of Electrical and Electronics Engineers (IEEE), 2011)
Multipulse rectifier topologies based on autoconnections are increasingly applied as interface stages between mains and power electronics converters. These topologies are attractive and cost-effective solutions for meeting the requirements of low total harmonic distortion of line current and high power factor. Furthermore, as only a small fraction of the total power required by the load is processed in the magnetic core, the overall resulting volume and weight are reduced. This paper proposes a mathematical analysis based on phasor diagrams that results in a single and general expression capable of unifying all delta and wye step-up or step-down autotransformer connections for 12-and 18-pulse ac-dc converters. The expression obtained allows the choice of a wide range of input/output voltage ratio for step-up or step-down autotransformer, and this general expression is also presented in a graphical form for each converter. Moreover, it simplifies the procedure for determining turn ratios and polarities for all windings of the autotransformer. A routine for easy and fast calculations is developed and validated by a design example. Finally, experimental results are presented along with comments on a 6-kW 220-V line voltage, 400-V rectified voltage, and 18-pulse delta-autoconnected prototype.
Keywords: Autotransformer; multipulse topologies; power factor correction; rectifiers